Optimization Of Online Motorcycle Taxi Driver Partner Registration Services At PT XYZ Bali Branch Office - Ni Kadek Ratna Puspitasari; Ni Ketut Purnawati (International Journal of Management Research and Economics, 2025)
This study aims to determine the optimal queue system configuration for online motorcycle taxi driver partner registration services at the PT XYZ Bali Branch Office using a quantitative approach. Data on arrival time, service time, and operational costs were analyzed through queuing theory using the POM-QM software. The analysis results show that although phases 1, 2, and 4 meet efficiency criteria (utilization below 70%), reducing the number of servers in phases 1 and 2 can lower operational costs, as the queuing cost is lower than the service cost. Meanwhile, phase 3 shows a high utilization rate (80%), but adding a server increases the total cost. Therefore, the study recommends implementing an interchange schedule to dynamically allocate servers during peak hours to maintain a balance between cost efficiency and service capacity. Additionally, the implementation of self-service in phase 2 is proposed to enhance efficiency without reducing service capacity, with experimental results showing an increase in service rates from 2 to 7 registrants per hour. These findings contribute to the development of a more efficient and applicable queuing model and serve as a reference for companies in improving service quality and registrant satisfaction.